The Views and Movement of the Earth Liberation Front (ELF) Movement towards Global Capitalism - Hakiki, Falhan; Nasution, Uswatun Hasanah (Jurnal Politik, 2022)
The Earth Liberation Front (ELF) movement was originally part of the Earth First! Movement and uses agitative and collaborative rhetoric in its actions. However, in 1992, the ELF broke away from Earth First! by changing its methods to those of direct action, attacking entities and symbols that represent global capitalism. The ELF’s departure becomes an exciting starting point to analyze the ELF’s view toward global capitalism through qualitative research methods. We used a framework encompassing deep ecology, social movements, and international structures. In the typology of social movements, the ELF movement belongs to the revolutionary deep ecology movement typology, which radically fights the causes of environmental damage. The ELF’s view of the international structure can be seen from three views. First, the ELF considers that the state system formed is a form of capitalism that has damaged the environment. Second, on the level of international society, the ELF has formed solidarity with its existing network in more than 20 countries. Third, on the level of world society, ELF seeks revolutionary social transformation that replaces the existing capitalist order with an order of total liberation. However, the actions and views of the ELF movement have not successfully changed the structure of the existing capitalist order.